Sazer-Fredin index – an effective method of assessing young pigs for feeding and meat qualities - Khalak, V.; Gutyj, B.; Il’chenko, M. (Scientific Progress & Innovations, 2023)
The purpose of the work was to investigate the fattening and meat quality of young pigs of different intrabreed differentiation according to the Sazer-Fredin index and, based on the obtained data, to calculate the economic efficiency of the results of the experiment. The research was carried out in the Dnipropetrovsk region and the animal husbandry laboratory of the State Institution “Institute of Grain Crops of the National Academy of Sciences”. The assessment of young pigs of the large white breed in terms of fattening and meat qualities was carried out considering the following indicators: average daily gain in live weight during the period of control fattening, g; the age of reaching 100 kg live weight, days; thickness of fat at the level of 6–7 thoracic vertebrae, mm; length of the cooled carcass, cm; the length of the bacon half of the chilled half-carcass, see. Control fattening of young pigs was carried out in farm conditions, according to M. D. Berezovsky and I. V. Khatka's method (2005). It was established that the young pigs of the large white breed of the controlled population belong to the elite class by the age of reaching a live weight of 100 kg, the Thickness of the lard at the level of 6–7 thoracic vertebrae, and the length of the chilled carcass. Taking into account the intrabreed differentiation according to the Suzer-Fredin index, it was established that the young pigs of experimental group I prevailed over peers of II in terms of the average daily gain of live weight during the period of control fattening by 4.23 %, the age of reaching a live weight of 100 kg – 1.83 %, the Thickness of lard by the level of 6–7 thoracic vertebrae – 14.47 mm and the length of the chilled carcass – 0.31 %. The leading indicators of the average daily increase in live weight during the period of control fattening and the length of the chilled carcass and the minimum values of the age of reaching the live weight of 100 kg and the Thickness of lard at the level of 6–7 thoracic vertebrae were found in young pigs of group I-b. The criterion for selecting highly productive animals according to the Sazer-Fredin index is young pigs with a variability of the specified mathematical model from +0.089 to +0.591 points. The pairwise correlation coefficient between young pigs' fattening and meat qualities and the Sazer-Fredin index ranges from -0.413 (tr=2.93) to +0.248 (tr=1.66). The maximum increase in additional production was obtained from young pigs of the first experimental group according to the Sazer-Fredin index (+1.47 %). The value of additional products obtained from young pigs of the specified group provided that the sales price for 1 kg of live weight of young pigs at the time of the study was UAH 67.4. is + UAH 101.93/head.